Structural organization of the social paper wasp (Hymenoptera: Polistinae) assemblage along a latitudinal gradient in the Atlantic Rainforest: correlating fauna partitioning to biodiversity centers - Santos, Eduardo Fernando dos [UNESP]; Noll, Fernando Barbosa [UNESP]; Ferreira Brandao, Carlos Roberto (Springer, 2016)
Based on species endemism, three biodiversity centers, called Ecological Corridors have been proposed as one of the main conservation strategies for the Atlantic Rain Forest. This study tested whether the organization of the social paper wasp assemblage fits those centers. A standardized protocol was used for sampling the social paper wasp fauna. The structural organization was estimated by Nonmetric Multidimensional Scaling (NMDS) based on the similarity indexes of Sorensen (qualitative data) and Morisita-Horn (quantitative data). Regressive models were applied to the first axes' site scores of the NMDS, to the latitudinal and altitudinal variations, and to the speciation and immigration probabilities predicted by the neutral theory for a metacommunity. Our results indicated that the social paper wasp assemblage is organized in a continuum, with two distinct biodiversity centers. The organization of the assemblage along the gradient was dependent on latitudinal and altitudinal variations and their interactions, and also on the speciation and immigration probabilities. Several studies have demonstrated that the current biodiversity patterns of the Atlantic Forest might be explained by the past climate and, consequently, by the connection between the Amazon and the Atlantic Forest. In addition, speciation and immigration probabilities strongly influence the compositional and structural variations of the social paper wasp assemblage along the latitudinal gradient.
Keywords: Atlantic Forest; Epiponini; Mischocyttarini; Polistini; Predatory wasp; Vespidae